3D Cell Cultures: Evolution of an Ancient Tool for New Applications - Cacciamali, Andrea; Villa, Riccardo; Dotti, Silvia (Frontiers in Physiology, 2022)
Recently the research is undergoing a drastic shift in the application of the animal model as a unique strategy of investigation considering an alternative approach for the development of a science for the future. Cell cultures represent a consolidated in vitro method, but also a springboard for more advanced systems. 2D cell cultures do not faithfully reproduce the environment and cell structure. 3D cell culture systems were then developed to mimic accurately the in vivo conditions and provide more realistic information than 2D model. Bioengineering has made a major contribution in the context of 3D systems using scaffolds that contribute to mimic the microenvironments where cells naturally reside, supporting mechanical, physical and biochemical requirements for cell growth and function. Organoids are stem cell-derived, self-organizing 3D cultures that phenocopy architecture and functionality of different tissues. ECM and medium are essential for organoids development and growth; they are crucial to recapitulate the signaling pathways of the stem cell niche in vivo, provide the correct molecular clues and guide their expansion and differentiation. Bioreactors, generating dynamic flows between distinct cell populations, allow an efficient communication between biological components. Bioreactors ensure an assessment of the microenvironment at pre-established times, without affecting the cellular components, allowing long-term studies on cell-cell interactions, on metabolic profiles, on pathological phenotypes or on the effect of substances on the substrate of interest. Also the organ-on-a-chip technology, based on microfluidic devices, proposes a new model of in vitro organ. The microfluidic system reflects the physiological flows, mimicking the target organ considered in an even more reliable way. Bioprinting is the device that can provide bioengineering support to some of the 3D systems described above by transferring and assembling cells, as bioink, in order to produce more complex structures such as tissues or scaffolds for three-dimensional cell cultures. All these techniques prove to be excellent candidates in the development of alternative methods to animal experimentation as well as revolutionizing cell culture technology. 3D systems will therefore be able to provide new ideas for the study of cellular interactions both in basic and more specialized research, in compliance with the 3R principle.